The struggle for rights anthropological reflections on what is and what ought to be - Gatmaytan, Augusto B. (2019)
This introduction to this human rights-themed issue of the Aghamtao journal provides an overview of the articles, most of which were presented during the 39th Annual Convention of the UGAT. It suggests that the human rights situation in the Philippines can be productively viewed as a "battlefield where various groups re/negotiate the meaning of 'human rights', such that the various articles' discussion of 'what is' (the conditions obtaining in the lives of the authors' interlocutors) can be seen as the product of such negotiations, and that 'what ought to be' emancipation from those conditions. This raises the question of how anthropologists and other social scientists ought to respond to this, the challenge of our times.